2015
DOI: 10.17849/insm-45-02-075-080.1
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Screening Independently Predicts All-Cause Mortality

Abstract: Objective .- Determine if the addition of hemoglobin testing improves risk prediction for life insurance applicants. Method .- Hemoglobin results for insurance applicants tested from 1993 to 2007, with vital status determined by Social Security Death Master File follow-up in 2011, were analyzed by age and sex with and without accounting for the contribution of other test results. Results .- Hemoglobin values ≤12.0 g/dL (and possibly ≤13.0 g/dL) in females age 50+ (but not age <50) and hemoglobin values ≤13.0 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Importantly, HDL-C exerts several physiological roles, prevents oxidation of LDL and inhibits expression of proinflammatory cytokines by macrophages, as well as expression of adhesion molecules by endothelial cells,44–46 and it is inversely associated with both all-cause and CVD mortality risks 18 19. Moreover, it is likely not coincidental nor trivial that the field of life insurance medicine recognises and prioritises the importance of HDL-C over LDL-C in determining underwriting classifications 16 17 47. Unfortunately, from a public health perspective, a meta-analysis of 31 randomised controlled trials on the use of HDL-C modifying treatments showed little to no effect on cardiovascular and all-cause mortality 48…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, HDL-C exerts several physiological roles, prevents oxidation of LDL and inhibits expression of proinflammatory cytokines by macrophages, as well as expression of adhesion molecules by endothelial cells,44–46 and it is inversely associated with both all-cause and CVD mortality risks 18 19. Moreover, it is likely not coincidental nor trivial that the field of life insurance medicine recognises and prioritises the importance of HDL-C over LDL-C in determining underwriting classifications 16 17 47. Unfortunately, from a public health perspective, a meta-analysis of 31 randomised controlled trials on the use of HDL-C modifying treatments showed little to no effect on cardiovascular and all-cause mortality 48…”
Section: Discussionmentioning
confidence: 99%
“… 18 19 Moreover, it is likely not coincidental nor trivial that the field of life insurance medicine recognises and prioritises the importance of HDL-C over LDL-C in determining underwriting classifications. 16 17 47 Unfortunately, from a public health perspective, a meta-analysis of 31 randomised controlled trials on the use of HDL-C modifying treatments showed little to no effect on cardiovascular and all-cause mortality. 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dass Leberwerterhöhungen mit vermehrter Mortalität und Begleiterkrankungen einhergehen, ist inzwischen von diversen Arbeiten belegt worden 2 5 6 7 8 9 10 . Verbreitete Ursachen sind Alkoholabusus, Medikamenteneinnahme, die nichtalkoholische Leberverfettung und Virushepatitiden 11 12 13 14 .…”
Section: Introductionunclassified
“…Verschiedene Arbeiten konnten belegen, dass Leberwerterhöhungen mit vermehrter Mortalität einhergehen [4][5][6][7][8][9]. Häufige Ursachen sind Alkoholabusus, Medikamenteneinnahme, die nichtalkoholische Leberverfettung und Virushepatitiden [10][11][12][13].…”
Section: Introductionunclassified